Enhancement of posterior brain functional networks in bilingual older adults. Issue 2 (26th March 2020) - de Frutos-Lucas, Jaisalmer; López-Sanz, David; Cuesta, Pablo; Bruña, Ricardo; de la Fuente, Sofía; Serrano, Noelia; López, María Eugenia; Delgado-Losada, María Luisa; López-Higes, Ramón; Marcos, Alberto; Maestú, Fernando
Abstract: Bilingualism has been said to improve cognition and even delay the onset of Alzheimer's disease (AD). This research aimed to investigate whether bilingualism leaves a neurophysiological trace even when people are highly educated. We expected bilinguals to present better preserved brain functional networks, which could be a trace of higher cognitive reserve. With this purpose, we conducted a magnetoencephalographic study with a group of healthy older adults. We estimated functional connectivity using phase-locking value and found five clusters in parieto-occipital regions in which bilinguals exhibited greater functional connectivity than monolinguals. These clusters included brain regions typically implicated in language processing. Furthermore, these functional changes correlated with caudate volumes (a key region in language shifting and control) in the bilingual sample. Interestingly, decreased Functional Connectivity between posterior brain regions had already been identified as an indicator of aging/preclinical AD but, according to our study, bilingualism seems to exert the opposite effect.